CURRENT APPROACHES FOR HPV-ASSOCIATED CIN - Татьяна Владимировна Клинышкова; Ольга Николаевна Миронова (The Publishing House Medicine and Enlightenment, 2020)
The aim of the study was to determine the frequency of expression of р16/Ki-67 in the cervical epithelium of patients with HPV-associated CIN of various degrees according to immunocytochemical studies in comparison with patients without cervical pathology. Materials and methods. The study included 62 women with cervical HPV infection and 13 women in the control group. Patients with CIN 1 formed the 1st main group (n = 21), women with CIN2-CIN3 - the 2nd main group (n = 26), and the comparison group consisted of patients with latent HPV infection (n = 15). Research methods: liquid сytology, colposcopic, histological research; methods for determining HPV BP DNA; immunocytochemical research to determine the double staining of р16/Ki-67 markers, statistical analysis. Results. Against the background of HPV infection, both in the 1st main group of patients with CIN1 and in the comparison group of patients with NILM, isolated cases of double staining of P16 and Ki-67 markers were recorded without significant differences between the groups (p = 0.44). In the 2nd main group of patients with CIN2, CIN3, co-expression of p16 and Ki-67 was observed in every second woman, it dominated relative to the 1st group and the comparison group (p = 0.003, p = 0.005, respectively). In the absence of HPV, the control group found that there was no double staining of markers. Conclusion. There were no differences in coexpression in CIN1 compared to latent HPV infection and the control group. When CIN 2+ is associated with HPV BP, the frequency of immunocytochemical confirmation of P16/Ki-67 expression is increased compared to CIN1, which increases the risk of precancerous progression. When choosing a differentiated management strategy for рatients with CIN on the background of HPV, it is necessary to take into account the data of the proliferative potential of the cervical epithelium.